P04.13 Prognostic role of single stranded DNA binding protein 2 in IDH wild type lower grade glioma. (6th September 2019) - Chai, Y; Liu, W; Hu, L; Zhang, Y; Liang, P
Abstract: Comprehensive and integrative characterizations of genomic analysis including somatic alterations and molecular subtypes of glioma have been established. However, diffuse gliomas (World Health Organization grades II and III, hereafter referred to collectively as lower-grade gliomas, LGG) consist of highly variable clinical behaviors, leading to emerging studies to identify prognostic factors. Through comparative analyses of 516 cases of primary LGG patients from The Cancer Genome Atlas (TCGA) dataset, we reported that the expression level and methylation level of SSBP2 (encoding single stranded DNA-binding protein 2) gene vary among LGG patients and SSBP2 expression or gene body methylation can be served as prognostic biomarkers for LGG survival. Cox regression results confirmed that SSBP2 as an independent predictor of survival in LGG, with a cox coefficient of 0.534 indicating a worse prognosis. Furthermore, lower-grade glioma was statistically ranked first among 21 different cancer types according to the FDR correction. We further investigated the combination of SSBP2 with other known genetic prognostic factors(IDH mutation and 1p19q co-deletion) of LGG. By matching gene expression profile of LGG patients, IDH-mutant gliomas had decreased expression of SSBP2 compared with IDH-wildtype gliomas and 1p19q intact gliomas had increased expression of SSBP2 compared with 1p19q codeletion gliomas. Moreover, we found that the combination of IDH or 1p19q status with SSBP2 identified LGG subsets with significantly diverse survival effects. Patients with low SSBP2 expression had significantly better 5-, 10-, and 15-year OS in IDH wild type, but not in the cohorts of IDH mutant. Our findings offer an explanation for the specificity of SSBP2 effect on survival rate in IDH wild type LGG patients.